Biochemical, Clinical, and Genetic Characteristics of Short/Branched Chain Acyl-CoA Dehydrogenase Deficiency in Chinese Patients by Newborn Screening - Lin, Yiming; Gao, Hongzhi; Lin, Chunmei; Chen, Yanru; Zhou, Shuang; Lin, Weihua; Zheng, Zhenzhu; Li, Xiaoqing; Li, Min; Fu, Qingliu (Frontiers in Genetics, 2019)
Short/branched chain acyl-CoA dehydrogenase deficiency (SBCADD) is an autosomal recessive disorder of impaired isoleucine catabolism caused by mutations in the ACADSB gene. There are limited SBCADD cases worldwide and to date no Chinese patients with SBCADD have been reported. The aim of this study was to investigate the biochemical, clinical information, and genotypes of twelve patients with SBCADD in China for the first time. The estimated incidence of SBCADD was 1 in 30,379 in Quanzhou, China. The initial newborn screening (NBS) results revealed that all patients showed slightly or moderately elevated C5 concentrations with C5/C2 and C5/C3 ratios in the reference range, which has the highest risk of being missed. All patients who underwent urinary organic acid analysis showed elevation of 2-methylburtyrylglycine in urine. All patients were asymptomatic at diagnosis, and had normal growth and development during follow-up. Eight different variants in the ACADSB gene, including five previously unreported variants were identified, namely c.596A>G (p.Tyr199Cys), c.653T>C (p.Leu218Pro), c.746del (p.Pro249Leufs*15), c.886G>T (p.Gly296*) and c.923G>A (p.Cys308Tyr). The most common variant was c.1165A>G (33.3%), followed by c.275C>G (20.8%). All previously unreported variants may cause structural damage and dysfunction of SBCAD, as predicted by bioinformatics analysis. Thus, our findings indicate that SBCADD may be more frequent in the Chinese population than previously thought and newborn screening, combined with genetic testing is important for timely diagnosis. Although the clinical course of Chinese patients with SBCADD is likely benign, longitudinal follow-up may be helpful to better understand the natural history of SBCADD.